1968
DOI: 10.1002/mana.19680360502
|View full text |Cite
|
Sign up to set email alerts
|

Uniform Structures on the Lattices of Open Sets

Abstract: Eingegangen a m 1. 3. 1966) Intr odue tio n In 1936, 31. H. STOKE [4] proved that every topological space can be iiiade into a To-space by identifying topologically indistinguishable points. The topology of the resulting space is lattice isomorphic t o that of the original space. An investigation into the effect of STOXE'S construction on the uniformities (if any) which induce the topology of the original space revealed that there is a nice 1 -1 correspondence between the uniformities compatible with the origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1981
1981
1981
1981

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Note that when as and y are distinct points in S, then x ^ y iff x } y eX and x ~ y in X. Thus ^ determines the members of ϊ 7 , with the identification of {t} with £ whenever ίeT\7. It is easy to show that the quotient topology on T agrees with c^f and that (X, ^) is a dense subspace of (S, SS).…”
Section: The T^identification Of (S And*) and (X ^) Is Densely Embeddmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that when as and y are distinct points in S, then x ^ y iff x } y eX and x ~ y in X. Thus ^ determines the members of ϊ 7 , with the identification of {t} with £ whenever ίeT\7. It is easy to show that the quotient topology on T agrees with c^f and that (X, ^) is a dense subspace of (S, SS).…”
Section: The T^identification Of (S And*) and (X ^) Is Densely Embeddmentioning
confidence: 99%
“…Therefore E = g~\g(E)) and g{E) e JT Hence JTc gf. Then there is ITeJ3T such that It is noted that Theorem 3.5 can also be proved from Theorem 2.1 in [7]. 4* Unique compatible uniformity and proximity* Early in the study of uniform spaces it was observed that a compact, completely regular topological space admits exactly one compatible uniformity [8,Theorem 20.38].…”
Section: X Y) Ehf)(sx S) Then (D(x) D{y)) = {F{x\ F(y)) E F(h) Tomentioning
confidence: 99%